2018
DOI: 10.1109/tpel.2017.2730038
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoff Study of Heat Sink and Output Filter Volume in a GaN HEMT Based Single-Phase Inverter

Abstract: Abstract-This paper presents the trade-off study of heat sink and output filter volume of a GaN HEMT based single phase inverter. The selected topology is three-level Active Neutral point Clamped (ANPC) inverter, and the main aim is to explore the benefits of the GaN HEMTs at 600 V blocking class on the system level efficiency, and power density under wide range of operating conditions. The paper starts by introducing the inverter topology, selected PWM scheme and followed by the device features, static and dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In particular, is has been shown that the switching energy is virtually independent of the baseplate temperature over a broad range of temperature values. This finding confirms previous observations on lower voltage SiC MOSFETs, for which this particular feature has already been proven to be associated with disruptive possibilities to optimize system level power densities by joint optimization of the switching frequency and the heat-sink [4]. Here, results for the parallel operation of the transistors and their body-diodes are presented.…”
Section: Experimental Testingsupporting
confidence: 90%
“…In particular, is has been shown that the switching energy is virtually independent of the baseplate temperature over a broad range of temperature values. This finding confirms previous observations on lower voltage SiC MOSFETs, for which this particular feature has already been proven to be associated with disruptive possibilities to optimize system level power densities by joint optimization of the switching frequency and the heat-sink [4]. Here, results for the parallel operation of the transistors and their body-diodes are presented.…”
Section: Experimental Testingsupporting
confidence: 90%
“…The topology of the above 3L-ANPC GaN inverter is shown in Because GaN HEMT has capability of reverse conduction, no parallel diodes needed. One PWM control method described in [2] was used to control this 3L-ANPC inverter. Synchronous rectification applied to decrease the conduction loss.…”
Section: Control Methods Of 3l-anpc Invertermentioning
confidence: 99%
“…From that same perspective, this paper reports on the learning done in recent years in some representative applications selected from the renewable energy applications domain (PV and wind). The findings clearly indicate that significant incremental benefits (not disruptive) can be drawn from WBG technology already as a drop-in replacement for Si, even with conventional standardized packaging solutions [1][2][3][4][5][6]. The higher initial price of the semiconductors is counter-balanced by savings in the filter elements and cooling, as well as by the possibility to do without free-wheeling diodes even in higher-voltage applications.…”
Section: Introductionmentioning
confidence: 94%
“…Because of the current and voltage rating involved, 650 V discrete transistors in the TO247 package were chosen for the main switches. This enabled a straightforward benchmark within the same exact power cell design with all available technologies [3][4][5], including Si IGBTs, SiC MOSFETs, and GaN HEMTs (gate injection type, GIT). The highest performance was achieved with GaN, with a small margin over SiC mainly because of the smaller parasitic capacitances and better switching, whereas both GaN and SiC decidedly outperformed Si.…”
Section: Inverter Performance and Power Density Trade-offmentioning
confidence: 99%